2002
DOI: 10.1523/jneurosci.22-14-06114.2002
|View full text |Cite
|
Sign up to set email alerts
|

Diets Enriched in Foods with High Antioxidant Activity Reverse Age-Induced Decreases in Cerebellar β-Adrenergic Function and Increases in Proinflammatory Cytokines

Abstract: Antioxidants and diets supplemented with foods high in oxygen radical absorbance capacity (ORAC) reverse age-related decreases in cerebellar beta-adrenergic receptor function. We examined whether this effect was related to the antioxidant capacity of the food supplement and whether an antioxidant-rich diet reduced the levels of proinflammatory cytokines in the cerebellum. Aged male Fischer 344 rats were given apple (5 mg dry weight), spirulina (5 mg), or cucumber (5 mg) either in 0.5 ml water by oral gavage or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 29 publications
3
86
0
Order By: Relevance
“…Although oxidative stress is one important possibility (Gemma et al, 2002), a new candidate mechanism, demyelination, is suggested by the findings here that genes for myelin and cholesterol synthesis were upregulated in normal brain aging (Table 1B, online Table 4). That is, because upregulation of myelin synthesis programs in adult animals is often stimulated by demyelination (Kristensson et al, 1986), the myelin program activation seen here might well be a compensatory response to an underlying demyelinating process.…”
Section: Myelin Turnover As An Inflammatory Triggermentioning
confidence: 86%
See 1 more Smart Citation
“…Although oxidative stress is one important possibility (Gemma et al, 2002), a new candidate mechanism, demyelination, is suggested by the findings here that genes for myelin and cholesterol synthesis were upregulated in normal brain aging (Table 1B, online Table 4). That is, because upregulation of myelin synthesis programs in adult animals is often stimulated by demyelination (Kristensson et al, 1986), the myelin program activation seen here might well be a compensatory response to an underlying demyelinating process.…”
Section: Myelin Turnover As An Inflammatory Triggermentioning
confidence: 86%
“…Several biological processes have been associated with normal brain aging and neurodegenerative conditions, including inflammatory responses (Rogers et al, 1996;Murray and Lynch, 1998;Hauss-Wegrzyniak et al, 2000;Andreasson et al, 2001;Finch et al, 2002;Gemma et al, 2002;Wyss-Coray and Mucke, 2002), oxidative stress (Carney et al, 1991;Butterfield et al, 1999;Bickford et al, 2000;Nicolle et al, 2001;Wang et al, 2001), reduced mitochondrial function (Nicotera and Orrenius, 1998;Wallace, 2001), and altered Ca 2ϩ regulation (Landfield and Pitler, 1984;Michaelis et al, 1984;Gibson and Peterson, 1987;Khachaturian, 1989;Disterhoft et al, 1993;Franklin and Johnson, 1994;Lipton and Rosenberg, 1994;Foster and Norris, 1997;Nicotera and Orrenius, 1998;Verkhratsky and Toescu, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, results of the present study demonstrated that the aged rats exhibited significant higher brain MDA level than the young. Increased levels of MDA have also been found in the aged canine brain [37] as well as in the hippocampus and cerebellum of aged rodents [38]. In order to protect cells from oxidative damage, aerobic metabolism generally depends on a stringent control of ROS by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Based primarily on MMSE criteria (35,46), subjects were categorized initially into four groups, termed ''Control'' (MMSE Ͼ25), ''Incipient AD'' (MMSE 20-26), ''Moderate AD'' (MMSE [14][15][16][17][18][19], and ''Severe AD'' (MMSE Ͻ14) ( Table 1). Several borderline cases (e.g., MMSE ϭ 26) were assigned based on NFT, amyloid plaque, and Braak stage data.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple processes have been implicated in AD, notably including abnormal ␤-amyloid (A␤) production (1-7), tau hyperphosphorylation and neurofibrillary tangles (NFTs) (8,9), synaptic pathology (10)(11)(12), oxidative stress (13)(14)(15), inflammation (5,(16)(17)(18)(19), protein processing or misfolding (20,21), calcium dyshomeostasis (15,(20)(21)(22)(23)(24)(25)(26), aberrant reentry of neurons into the cell cycle (27,28), cholesterol synthesis (29,30), and effects of hormones (23,31) or growth factors (17,32). Nevertheless, the pathogenic factors that initiate these processes remain elusive.…”
mentioning
confidence: 99%